An evaluation of multidrug-resistant Escherichia coli isolates in urinary tract infections from Aguascalientes, Mexico: cross-sectional study - Flor Y. Ramírez-Castillo; Adriana C. Moreno-Flores; Francisco J. Avelar-González; Francisco Márquez-Díaz; Josée Harel; Alma L. Guerrero-Barrera (BMC, 2018)
Abstract Background Uropathogenic Escherichia coli (UPEC) are one of the main bacteria causing urinary tract infections (UTIs). The rates of UPEC with high resistance towards antibiotics and multidrug-resistant bacteria have increased dramatically in recent years and could difficult the treatment. Methods The aim of the study was to determine multidrug-resistant bacteria, antibiotic resistance profile, virulence traits, and genetic background of 110 E. coli isolated from community (79 isolates) and hospital-acquired (31 isolates) urinary tract infections. The plasmid-mediated quinolone resistance genes presence was also investigated. A subset of 18 isolates with a quinolone-resistance phenotype was examined for common virulence genes encoded in diarrheagenic and extra-intestinal pathogenic E. coli by a specific E. coli microarray. Results Female children were the group most affected by UTIs, which were mainly community-acquired. Resistance to trimethoprim-sulfamethoxazole, ampicillin, and ampicillin-sulbactam was most prevalent. A frequent occurrence of resistance toward ciprofloxacin (47.3%), levofloxacin (43.6%) and cephalosporins (27.6%) was observed. In addition, 63% of the strains were multidrug-resistant (MDR). Almost all the fluoroquinolone (FQ)-resistant strains showed MDR-phenotype. Isolates from male patients were associated to FQ-resistant and MDR-phenotype. Moreover, hospital-acquired infections were correlated to third generation cephalosporin and nitrofurantoin resistance and the presence of kpsMTII gene. Overall, fimH (71.8%) and fyuA (68.2%), had the highest prevalence as virulence genes among isolates. However, the profile of virulence genes displayed a great diversity, which included the presence of genes related to diarrheagenic E. coli. Out of 110 isolates, 25 isolates (22.7%) were positive to qnrA, 23 (20.9%) to qnrB, 7 (6.4%) to qnrS1, 7 (6.4%) to aac(6')lb-cr, 5 (4.5%) to qnrD, and 1 (0.9%) to qnrC genes. A total of 12.7% of the isolates harbored bla CTX-M genes, with bla CTX-M-15 being the most prevalent. Conclusions Urinary tract infection due to E. coli may be difficult to treat empirically due to high resistance to commonly used antibiotics. Continuous surveillance of multidrug resistant organisms and patterns of drug resistance are needed in order to prevent treatment failure and reduce selective pressure. These findings may help choosing more suitable treatments of UTI patients in this region of Mexico.